2020
DOI: 10.1113/ep088898
|View full text |Cite
|
Sign up to set email alerts
|

Global REACH 2018: The carotid artery diameter response to the cold pressor test is governed by arterial blood pressure during normoxic but not hypoxic conditions in healthy lowlanders and Andean highlanders

Abstract: The impact of oxygen on the circulatory responses to a cold pressor test (CPT) in lowlanders and Andean highlanders remains unknown. Our hypotheses were as follows: (i) in lowlanders, acute normobaric and hypobaric hypoxia would attenuate the common carotid artery (CCA) diameter response to the CPT compared with normobaric normoxia; (ii) Andean highlanders would exhibit a greater CCA diameter response compared with lowlanders; and (iii) a positive relationship between CCA diameter and blood pressure in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
2
0
0
Order By: Relevance
“…(2) the systemic vasoconstrictor response to sympathetic activation is augmented during hypoxaemia in men, but not in women; and (3) the local forearm vasoconstrictor response to sympathetic activation is attenuated during hypoxaemia in women only. Our results in men confirm previous findings in cohorts of predominantly male participants (Dinenno et al, 2003;Tan et al, 2013;Tymko et al, 2020;Rowell & Blackmon, 1986), and we now extend them to highlight sex-related differences in neurovascular control during systemic hypoxia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…(2) the systemic vasoconstrictor response to sympathetic activation is augmented during hypoxaemia in men, but not in women; and (3) the local forearm vasoconstrictor response to sympathetic activation is attenuated during hypoxaemia in women only. Our results in men confirm previous findings in cohorts of predominantly male participants (Dinenno et al, 2003;Tan et al, 2013;Tymko et al, 2020;Rowell & Blackmon, 1986), and we now extend them to highlight sex-related differences in neurovascular control during systemic hypoxia.…”
Section: Discussionsupporting
confidence: 90%
“…The CPT is a well-established sympathoexcitatory stimulus used to assess α-adrenergic receptor-mediated vasoconstriction in humans (Dinenno et al, 2001;Frank & Raja, 1994;Kooijman et al, 2009). Similar to previous studies, including those utilizing the CPT, we found the vascular response to sympathetic activation was maintained (Figure 2a; Dinenno et al, 2003;Tymko et al, 2020;Roweel & Blackmon, 1986) or even enhanced (Figure 1a; Tan et al, 2013) in healthy young men during systemic hypoxia. Although the majority of prior work in humans has focused on the skeletal muscle vasculature, vascular responsiveness to sympathetic activation during systemic hypoxia may differ by vascular bed (Gonzales et al, 2008).…”
Section: Discussionsupporting
confidence: 85%